2021
DOI: 10.1002/anie.202107155
|View full text |Cite
|
Sign up to set email alerts
|

Red‐Light‐Mediated Photoredox Catalysis Enables Self‐Reporting Nitric Oxide Release for Efficient Antibacterial Treatment

Abstract: Nitric oxide (NO) serves as a key regulator of many physiological processes and as a potent therapeutic agent. The local delivery of NO is important to achieve target therapeutic outcomes due to the toxicity of NO at high concentrations. Although light stimulus represents a non‐invasive tool with spatiotemporal precision to mediate NO release, many photoresponsive NO‐releasing molecules can only respond to ultraviolet (UV) or near‐UV visible light with low penetration and high phototoxicity. We report that cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
78
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(78 citation statements)
references
References 71 publications
0
78
0
Order By: Relevance
“…Gaseous signaling molecules (GSMs) such as nitric oxide (NO), carbon monoxide (CO), and hydrogen sulfide (H 2 S) have been known to not only play critical roles in regulating many physiological and pathological processes but also show unique therapeutic benefits to many diseases. [1] To overcome the inconvenience of gas storage and safely deliver GSMs to local tissues,m uch effort has been devoted to the development of various donor molecules,e nabling improved dose control and decreased systemic toxicity.T odate,aplethora of donors capable of releasing NO, [2] CO, [3] and H 2 S [4] have been developed, showing great promise in the treatment of cancers, rheumatoid arthritis,e tc. However,d espite great achievements,the simultaneous delivery of two or more GSMs has far less been explored, although it is well-known that different GSMs have asubtle interplay and interact with each other to maximize the regulatory effects in truly physiological conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Gaseous signaling molecules (GSMs) such as nitric oxide (NO), carbon monoxide (CO), and hydrogen sulfide (H 2 S) have been known to not only play critical roles in regulating many physiological and pathological processes but also show unique therapeutic benefits to many diseases. [1] To overcome the inconvenience of gas storage and safely deliver GSMs to local tissues,m uch effort has been devoted to the development of various donor molecules,e nabling improved dose control and decreased systemic toxicity.T odate,aplethora of donors capable of releasing NO, [2] CO, [3] and H 2 S [4] have been developed, showing great promise in the treatment of cancers, rheumatoid arthritis,e tc. However,d espite great achievements,the simultaneous delivery of two or more GSMs has far less been explored, although it is well-known that different GSMs have asubtle interplay and interact with each other to maximize the regulatory effects in truly physiological conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The combination of [Cu(dap) 2 ] + and DCA complements and expands the known photochemical applications of these two individual components when used separately. 68 , 77 , 83 , 89 , 117 , 159 167 Red light-driven applications play important roles in other important contexts, for example, hydrogen production, 47 , 48 , 168 , 169 medical applications, 158 , 169 173 and polymerizations. 174 178 Now, red light as well as multiphoton excitation-based mechanisms seem to become of increasing interest for synthetic organic photoredox chemistry, 50 , 126 , 179 181 and we hope the insights gained from our work will be useful in that greater context.…”
Section: Discussionmentioning
confidence: 99%
“…To address this issue, Hu et al reported redlight-mediated photoredox catalysis for NO release from an N-nitrosoamine derivative. [157] In brief, the authors fabricated NO-releasing micelles by incorporating a photosensitizer palladium(II) tetraphenyltetrabenzoporphyrin (PdTPTBP) and Nnitrosoamine derivatives CouN(NO)-R into micelle cores as shown in (Figure 21). The 7-aminocoumarin derivatives were chosen as the NO-releasing scaffold for their relatively high NO loading content (≈10 wt%) and self-reporting NO release.…”
Section: Light-triggered Releasementioning
confidence: 99%
“…This study suggests a feasible strategy for fighting MDR tumors by using NIR to specifically control NO release from BNN6 and combine chemotherapeutics for tumor ablation. [157] Copyright 2021, Wiley-VCH.…”
Section: Light-triggered Releasementioning
confidence: 99%
See 1 more Smart Citation